Water Resources Change in Central-Western Argentina Under the Paris Agreement Warming Targets - Rivera, Juan A.; Naranjo Tamayo, Elizabeth; Viale, Maximiliano (Frontiers in Climate, 2020)
This study documents the projected changes in several components of the hydrological cycle in Central-Western Argentina (CWA) based on the simulations from the IPSL-CM6A-LR model for the warming levels proposed in the Paris Agreement. These warming levels represent the future increase in mean annual temperature of 1.5 and 2 °C compared to pre-industrial conditions. For this purpose, a set of low-emissions shared socioeconomic pathways (SSP) was selected. Our results show that the timing of reaching the 1.5 °C warming level would be between 2032 and 2036 in the CWA lowlands east of the Andes, while the timing of reaching this warming level in the Andes mountains of CWA is expected to be 10-15 years earlier as result of the enhanced warming with elevation. The 2 °C warming level would be before 2050 in the Andes mountains. Even following the more aggressive mitigation pathways available in the scientific literature (SSP1-1.9 and SSP1-2.6), the IPSL-CM6A-LR model ensemble shows a robust drying signal in the wintertime precipitation over the Andes mountains. This drying is a concerning result because imply a reduction of the scarce water resources draining to the adjacent semi-arid foothills. Our results also show that this drying should be linked to the poleward expansion of the Hadley Circulation. In the lowlands farther east from the Andes, the summertime monsoonal precipitation provide the water resources that are projected to increase under the selected emissions pathways. The expected changes in the analyzed components of the hydrological cycle would be strengthened under the 2 °C warming level, particularly the decline of snow amount and surface runoff in the Andes. The results of this study provide insights into the expected impacts of the 1.5 ° and 2 °C warming levels in the CWA regional water resources, which may set the stage for the new discussions of possible options to mitigate them at country and regional levels.